Modeling of Genome-Wide Polyadenylation Signals in Xenopus tropicalis - Zhu, Sheng; Wu, Xiaohui; Fu, Hongjuan; Ye, Congting; Chen, Moliang; Jiang, Zhihua; Ji, Guoli (Frontiers in Genetics, 2019)
Alternative polyadenylation (APA) is an important post-transcriptional modification event to process messenger RNA (mRNA) for transcriptional termination, transport and translation. In the present study, we characterized poly(A) signals in X. tropicalis using 70,918 highly confident poly(A) sites derived from 16,511 protein-coding genes to understand their roles in the regulation of embryo development and gender difference. We examined potential factors, including the gene length, the number of introns in a gene, and the intron length, that may affect the prevalence of APA. We observed 12 prominent poly(A) signal patterns, which accounted for approximately 92% of total APA sites in X. tropicalis. Among them, three patterns are specific to X. tropicalis so that they are absent in other animals such as human or mouse. We catalogued APA sites based on their genomic regions and developed a bioinformatics pipeline to identify over-represented signal patterns for each class. Then the schema of cis elements for APA sites in each genomic region was proposed. More importantly, APA usage is dramatically dynamic in embryos along five developmental stages and well-coordinated with the maternal to zygotic transition event. We used an entropy-based method to identify developmental stage-specific APA sites and identified significant signal patterns around specific sites and constitutive sites. We found that the APA frequency in different genomic regions varies with developmental stages and those sites located in intron or coding sequence regions contribute most to the dynamics of gene expression during developmental stages. This study deciphers the characteristics and poly(A) signal patterns for both canonical APA sites and non-canonical APA sites across different developmental stages and gender dimorphisms in X. tropicalis, providing new insights into the dynamic regulation of distal and proximal APA.